Effects of kratom (Mitragyna speciosa Korth.) in reducing risk-behaviors among a small sample of HIV positive opiate users in Malaysia. Issue 4 (4th November 2022) - Singh, Darshan; Narayanan, Suresh; Abdullah, Mohammad Farris Iman Leong; Vicknasingam, Balasingam
Abstract: Out-of-treatment HIV positive opiate users often engage in risky injecting and sexual behaviors. We sought the self-reported experiences on whether or not kratom ( Mitragyna speciosa Korth.) use was associated with a reduction in HIV risk behaviors among them. A convenience sample consisting of thirty-two HIV positive opiate users participated in the study. Of this, three-fifths (n = 20/32) used kratom to suppress opiate withdrawal, increase energy, as a heroin substitute, to reduce heroin dependence and self-treat psychological problems. More than one-third (38%) in the sample claimed that kratom use reduced their risky injecting and sexual behaviors. Given the small sample size, the perceived association between kratom use and the reduction in HIV risk behaviors could not be established more convincingly. However, the findings provide the basis for a broader-based study to evaluate the potential of kratom in curtailing HIV risk behaviors among HIV positive opiate users.